PENGARUH JAMINAN DAN DAYA TANGGAP TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN DRONE FIMI PADA PT HUGO PRIMA SAKTI KABUPATEN TANGERANG - Marchellia Dwi Rezaliani; Renny Anggraini (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Abstract. The purpose of this study is to determine the effect of guarantees and responsiveness partially and simultaneously on purchasing decisions for FIMI Drones at PT Hugo Prima Sakti, Tangerang Regency. This research method uses a quantitative description method, data collection techniques using questionnaires. In this study, the population is all FIMI Drone consumers at PT Hugo Prima Sakti, Tangerang Regency, totaling 2,000 from the latest data for the period 2022-2024 seen from the sales realization data of PT Hugo Prima Sakti, Tangerang Regency for one year. Using the 10% slovin formula, the sample is 95 respondents. Data analysis uses validity tests, reliability tests, classical assumption tests, multiple regression analysis, multiple correlation coefficient analysis, determination coefficient analysis and hypothesis testing. It can be stated that Guarantee (X1) has a significant effect on purchasing decisions (Y). The results of the calculation of the t-test value of the Guarantee variable (X1) with a t count of 5,142 and a significance of 0,000 are obtained. Because t count is greater than t table (5,142 > 1.985) and significance is less than 5% then Ha is accepted and H0 is rejected, It can be concluded that Responsiveness (X2) has a significant effect on Purchasing Decisions (Y). The results of the calculation of the t test value of the Responsiveness variable (X2) with a t count of 6,975 and a significance of 0,000. Because t count is greater than t table (6,975 > 1.985) and significance is less than 5% (0,000) then Ha is accepted and H0 is rejected. It can be said that Guarantee (X1), Responsiveness (X2) and together have a significant effect on Purchasing Decisions (Y). Based on the results of the analysis in the table above, namely the ANOVA test, the F count value is 69,090 while the F table (0.05) for n = 95 is 2.70. So, F count > F table (α 0.05) or 69,090 > 2.70, with a significance level of 0,000 because 0,000 < 0.05. Keywords: Guarantee, Responsiveness, Purchase Decision